Decision Making in Fuzzy Closed Loop Dual Channel Supply Chain - Mondal, Animesh; Kumar, Jana Ranjan; Kumar, Jana Dipak (Yugoslav Journal of Operations Research, 2023)
This paper discusses the optimal pricing and collecting decisions in a fuzzy environment of the three closed-loop dual-channel supply chain models where a manufacturer produces the original product from fresh materials and unfashionable products. The manufacturer sells the original products to the customers using direct and retail channels (forward dual channel). In the reverse channel, the manufacturer, third-party collector and retailer individually take responsibility for unfashionable products acquired from the market in the three models. Remanufacturing cost, product collecting cost and market demand are treated as fuzzy variables. The optimal decisions wholesale price, direct price, retail price and collection rate are derived using fuzzy set theory and game theory approach in the three decision models. Finally, numerical illustrations clarify the impact of the fuzzy degree parameters on the decision variables and the expected profits of the players. It is found that the manufacturer decision model is superior for receiving the maximum expected profits of the players and also being more convenient from the customer’s perspective.